Pengaruh laju aliran coolant campuran air dengan ethylene glycol terhadap laju perpindahan panas dan penurunan tekanan radiator otomotif - Bernadus Nanang Dwi Nuryanto; Tri Istanto; Wibawa Endra Juwana (Jurnal Teknik Mesin Indonesia, 2016)
This experimental study was conducted to examine the heat transfer rate and pressure drop on corrugated louver fin with triangular channel radiator. Radiator tube and fin were made of aluminium. Cold fluid flows verticaly from top side to bottom while air flows horizontaly (crossflow heat exchanger). Water and 20% Ethylene glycol were used as hot fluid (coolant) and maintained at constant temperature of 80 oC and varied at flow rate of 25 lpm, 30 lpm, 35 lpm, dan 40 lpm. Where as air was used as cold fluid having its velocity varied at 1.5 m/s, 2 m/s, 2,5 m/s and 3 m/s. And air intake temperature was maintained around 30 oC. The result shows the higher water flow rate in the radiator tube, resulting in higher value of heat transfer rate, and coolant pressure drop. Ethylene glycol mixing composition into the coolant, affects on decreasing the heat transfer rate. The highest heat transfer rate enhancement was obtained at water coolant usage. Ethylene glycol mixing affects the increasing coolant-side pressure drop.